2012
DOI: 10.3892/ol.2012.817
|View full text |Cite
|
Sign up to set email alerts
|

Lymphangiogenesis in non-Hodgkin’s lymphoma and its correlation with cyclooxygenase-2 and vascular endothelial growth factor-C

Abstract: Abstract. We aimed to investigate the correlations between lymphangiogenesis, cyclooxygenase (COX)-2 and vascular endothelial growth factor-C (VEGF-C) in non-Hodgkin's lymphoma (NHL) and their associations with the clinical parameters of patients. A total of 75 patients diagnosed with NHL were enrolled in this study. Of the 75 patients, 14 (18.7%) had low-grade and 61 (81.3%) had aggressive lymphoma. We examined the immunohistochemical expression of COX-2 and VEGF-C and estimated lymphangiogenesis by counting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 36 publications
1
9
0
Order By: Relevance
“…No correlations were observed between FCEAI, histological alterations, IBD and LGAL with COX-2 expression. Similar results have been obtained in canine IBD, and human lymphoma and IBD [ 44 , 46 , 58 60 ].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…No correlations were observed between FCEAI, histological alterations, IBD and LGAL with COX-2 expression. Similar results have been obtained in canine IBD, and human lymphoma and IBD [ 44 , 46 , 58 60 ].…”
Section: Discussionsupporting
confidence: 86%
“…However, other studies in canine lymphoma did not find COX-2 immunoreactivity [ 53 , 56 ]. Furthermore, studies in humans revealed that most of non-Hodgkin’s lymphoma (> 50% of cases) had COX-2 expression by tumour cells [ 58 60 ]. Thus, COX-2 upregulation in lymphomas has been associated with the aggressiveness, relapsed, worst response to therapy and less overall survival [ 58 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…Considering haematological malignancies, positive correlation between increased number of PDPN-positive vessels and disease progression was reported in Sézary syndrome, the most common, aggressive CTCL (33). Increased LVD was also associated with aggressive histology in non-Hodgkin's lymphomas (NHL) (23).…”
Section: Discussionmentioning
confidence: 99%
“…In breast, prostate and colon cancer increased expression of VEGF-C correlated with high lymphatic vessel density (LVD) and poor survival (16)(17)(18)(19)(20)(21). In haematological malignancies, increased lymphangio genesis was found to be correlated with aggressiveness and poor clinical outcome of lymphoma (22,23).…”
mentioning
confidence: 99%
“…It is also one of the key markers of disease outcome. Numerous studies published over the past decades showed a close relationship between the vascularization of the tumour, its histological grade and clinical progression and poor prognosis in non-Hodgkin's lymphomas (NHL) (25)(26)(27)(28). In contrast, relatively little attention was paid to primary CTCLs in the aspect of angio-and lymphangiogenesis.…”
Section: Discussionmentioning
confidence: 99%